The painting of Saint Gregory Nazianzen by Erasmus Quellinus II in Lima (1788) - Holguín Valdez, Anthony (2021)
This article studies the canvas of San Gregorio Nacianceno, signed by the Flemish painter Erasmus Quellinus II, which was in the church of the Jesuits in Cuzco before the expulsion from the Peruvian viceroyalty in 1767. The revised documentation has made it possible to follow the work from its arrival at the church of the Cuzco company and its subsequent events until its transfer to Lima in 1788. This study also provides an insight into the appraisal process of the Lima painters, their criteria and estimates of the artistic value of the work.